EVALUASI KEBIJAKAN MADRASAH IBTIDAIYAH NEGERI SEBAGAI SAT UAN KERJA KEMENTERIAN AGAMA - Wakhid Kozin; Nurudin Nurudin; Muhammad Rais (Badan Litbang dan Diklat Kementerian Agama RI, 2014)
The issue in this research is how the effectiveness of Madrasah Ibtidaiyah Negeri (MIN) as a working unit of the Ministry of Religious Affairs. This study aimed to evaluate the policies of Madrasah Ibtidaiyah Negeri as a working unit of the Ministry of Religious Affairs. This study used a mixed method (quantitative and qualitative). The findings in this study are: First, the process of learning in MIN is still good, despite its position as a workingunit (PIU). Second, management functions (planning, implementation and reporting of program) at MIN is good, despite many obstacles on the planning aspects of the program, although the process pays no regard to needs assessment and does not involve stakeholders more broadly. Third, MIN does not have proper personnel both in terms of quantity and quality. Fourth, with regard to accountability aspects of financial management accountability, MIN still experiences difficulties in an attempt to follow Government Accounting Standard (SAP). Fifth, the context of the arrangement of the future, most of the Heads of Office of Religious Affairs of Cities and Regencies and agree that MIN should remain a working unit, while the Principals agree that should remain a working unit. However, MIN effectiveness as a working unit requires structural support or the Deputy Head andTreasurer.